Phosphatases - Allen, Karen N. (Methods in enzymology, 2018)
High-energy phosphate ester bonds are often thought of as the energetic currency of the cell. Phosphoryl transfer is involved in processes ranging from the biosynthesis and catabolism of carbohydrates and polysaccharides, nucleic acids, and cofactors, to the regulation if cellular pathways. In addition, Phosphoryl groups on small-molecule metabolites confer important properties - providing excellent "handles" for enzyme bonding, trapping metabolic intermediates within the cell, and controlling the reversibility of metabolic pathways. The phosphorylation states of proteins also afford key control points for signal transduction and the regulation of myriad critical physiological processes. For this reason, kinases are extremely important therapeutic targets and there is significant interest in developing diverse approaches to regulate their function through small-molecule inhibitors. We present here the less studied but equally important complement of phosphate ester chemistry, namely the coordinated action of phosphatases. Phosphatases represent control points in pathways and new opportunities for use in chemoenzymatic synthesis. In many cases, such critical players may be functionally unannotated. However, there are many challenges in their study - spurring on the efforts described in this volume ... This volume of Methods in Enzymology on phosphatases which draws upon approaches from the varied disciplines of computational and organic chemistry, biophysics, biochemistry, bioinformatics, and cell biology to address the structure, mechanism, and regulation of phosphatases."--Preface.